(3GdeeJY aj GdJUQjas - (3GHf YUahQ , Ydj Hf eDef Hf eMeO GdMVQej GdGTHjdj, CHh GdMSf,J (B669 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG QCjJ GdfMhjjf aJQchG GdJCdja ajg s
(3BNQgG (B:s
(3ced cJGH GdJUQja hGdMeO ddg s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1822s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JQeje s
Keywords: (3GdUQas